Optimization of Ethanol Production from Palmyra Sap by Zymomonas mobilis using Response Surface Methodology (RSM) - RUTH CHRISNASARI; AGUSTIN KRISNA WARDANI; UNTUNG MURDIYATMO (Microbiology Indonesia, 2011)
Ethanol is believed to be one of the best alternatives to replace gasoline, because ethanol is a renewable energy source and environmentally friendly. The present study focuses on the optimization of palmyra sap as a source for ethanol production. Statistical experimental design using Box-Wilson central composite design (CCD) was used to optimize the quantitative effects of sugar, urea, and inoculum concentration on ethanol production. It was found that palmyra sap could be used as a substrate for ethanol production using Zymomonas mobilis (NRRL B-14234). A maximum ethanol concentration of 58.97 g L-1 was obtained after optimizing the parameters of fermentation. The optimum values of sugar, urea, and inoculums concentration were 206.01 g L-1, 3.16 g L-1, and 23.05% (v v-1), respectively, with ethanol yield of 0.3039 g g-1. A high similarity was observed between the predicted and experimental results, which reflected the accuracy and applicability of RSM to optimize the process for ethanol production.